26=-68x+42x

Simple and best practice solution for 26=-68x+42x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 26=-68x+42x equation:


Simplifying
26 = -68x + 42x

Combine like terms: -68x + 42x = -26x
26 = -26x

Solving
26 = -26x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '26x' to each side of the equation.
26 + 26x = -26x + 26x

Combine like terms: -26x + 26x = 0
26 + 26x = 0

Add '-26' to each side of the equation.
26 + -26 + 26x = 0 + -26

Combine like terms: 26 + -26 = 0
0 + 26x = 0 + -26
26x = 0 + -26

Combine like terms: 0 + -26 = -26
26x = -26

Divide each side by '26'.
x = -1

Simplifying
x = -1

See similar equations:

| 6v^2-11v-35=0 | | 3a-4b+c-d=0 | | ln(x+6)+ln(x+5)=ln(5) | | f(x)=2x^4-x^3+49x^2-25x-25 | | n-1.4n-1=6(n-2.3) | | C-32=71 | | x+(x+40)=110 | | 2ln(lnx)-ln(5lnx-6)=0 | | a-6.6=10.1 | | -17x+2(x+14)=-2 | | y^2=x^2-x^4 | | (X^8)-1=0 | | R+4=12 | | 6n+45=4n-15 | | f(x+4)=8(x+4)-2 | | (8+z)(5z+9)=0 | | -2-3x+5=16+2x+22 | | .75x=.51 | | 8.5x-12=6.5x-18 | | (4z+5)(4+z)=0 | | 27y^3+36y^2+12y= | | y=6x^2+7x-10 | | 8.5x-12=6.5-18 | | 6-2x+8y+4x-15y= | | 1-t+2.2t=5.9 | | m^2+10m+41=0 | | 0.5(x+6)+1.5(x-5)= | | z^2-20=0 | | 3(1+h)=3h-9 | | 7y^2+12y=0 | | .8x=43 | | 3s^3-16s+5= |

Equations solver categories